An unprecedented high-temperature-tolerance 2D laminar MXene membrane for ultrafast hydrogen sieving - Fan, Y.; Wei, L.; Meng, X.; Zhang, W.; Yang, N.; Jin, Y.; Wang, X.; Zhao, M.; Liu, Shaomin (Elsevier BV, 2019)
© 2018 Elsevier B.V. Exploring high selectivity molecular sieving membranes and the corresponding facile assembly methods are extremely critical for the gas separation. In this work, we demonstrated a high-temperature-tolerance 2D membrane for hydrogen sieving. This membrane was prepared by a vacuum-assisted filtration with a subsequent drying process in which all the manipulations were based on the ambient conditions. The XRD study indicates that the crystal structure is quite stable even at a wide temperatures range from 25 to 500 °C. The interlayer spacing of MXene membrane was shrank from 3.4 Å (25 °C) to 2.7 Å (500 °C) after such high temperature treatment, reinforcing the molecular sieving properties. The membrane exhibited the moderate H2 permeation of 2.05 × 10-7 mol m-2 s-1 Pa-1 and good selectivity of 41 for H2/N2 mixture at 320 °C. Benefiting from the excellent chemical stability of MXene membranes, no degradation was found for permeation and separation test up to 200 h. The high separation performance and the exceptional high-temperature stability mirror the 2D MXene membranes as a promising candidate for the separation of industrial gas mixtures containing hydrogen.